Inhibitory effect of the Kampo medicinal formula Yokukansan on acute stress-induced defecation in rats - Kanada Y (Dove Medical Press, 2018)
Yasuaki Kanada, Ayami Katayama, Hideshi Ikemoto, Kana Takahashi, Mana Tsukada, Akio Nakamura, Shogo Ishino, Tadashi Hisamitsu, Masataka Sunagawa Department of Physiology, School of Medicine, Showa University, Shinagawa-ku, Tokyo, Japan Objectives: Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder with symptoms of abnormal defecation and abdominal discomfort. Psychological factors are well known to be involved in onset and exacerbation of IBS. A few studies have reported effectiveness of traditional herbal (Kampo) medicines in IBS treatment. Yokukansan (YKS) has been shown to have anti-stress and anxiolytic effects. We investigated the effect of YKS on defecation induced by stress and involvement of oxytocin (OT), a peptide hormone produced by the hypothalamus, in order to elucidate the mechanism of YKS action. Methods and results: Male Wistar rats were divided into four groups; control, YKS (300 mg/kg PO)-treated non-stress (YKS), acute stress (Stress), and YKS (300 mg/kg PO)-treated acute stress (Stress+YKS) groups. Rats in the Stress and Stress+YKS groups were exposed to a 15-min psychological stress procedure involving novel environmental stress. Levels of plasma OT in the YKS group were significantly higher compared with those in the Control group (P < 0.05), and OT levels in the Stress+YKS group were remarkably higher than those in the other groups (P < 0.01). Next, rats were divided into four groups; Stress, Stress+YKS, Atosiban (OT receptor antagonist; 1 mg/kg IP)-treated Stress+YKS (Stress+YKS+B), and OT (0.04 mg/kg IP)-treated acute stress (Stress+OT) groups. Rats were exposed to acute stress as in the previous experiment, and defecation during the stress load was measured. Administration of YKS or OT significantly inhibited defecation; however, administration of Atosiban partially abolished the inhibitory effect of YKS. Finally, direct action of YKS on motility of isolated colon was assessed. YKS (1 mg/mL, 5 mg/mL) did not inhibit spontaneous contraction. Conclusion: These results suggested that YKS influences stress-induced defecation and that increased OT secretion may be a mechanism underlying this phenomenon. Keywords: Yokukansan, oxytocin, irritable bowel syndrome, acute stress, corticosterone, Kampo medicine